2013
DOI: 10.1177/1359105313482163
|View full text |Cite
|
Sign up to set email alerts
|

Mood enhancement in health-promoting non-aerobic exercise: The role of non-specific mechanisms

Abstract: Eighty participants took part in a 5-day intervention Qi Gong study to enhance well-being and were randomised to either positive or body focus and either high or low hand position. The high hand position improved negative affect and was reported more intrinsically motivating but was unrelated to perceived effort. Positive focus produced better positive affect. For all groups combined, intrinsic motivation and effort predicted all three outcomes. The association between expectancy and perceived benefit was medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…We did not ask patients why they considered particular techniques easier than others but the results are consistent with findings that adding positive content to relaxation techniques is helpful. 14 The qualitative data suggest that familiarity is an important component, and the ability to access the memory of previous relaxing and positive states mood states is helpful. “Counting” had a high mean rating and was ranked as the easiest to use by four out of 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…We did not ask patients why they considered particular techniques easier than others but the results are consistent with findings that adding positive content to relaxation techniques is helpful. 14 The qualitative data suggest that familiarity is an important component, and the ability to access the memory of previous relaxing and positive states mood states is helpful. “Counting” had a high mean rating and was ranked as the easiest to use by four out of 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol would likely be a good paradigm for the future study of placebo mechanisms, although efforts should be made to address what may have been a less than optimal manipulation of expectancy. Expectancy effects vary by study, and recent studies have similarly observed discrepant findings for expectancy influences (Gaitan-Sierra & Hyland, 2013). This study followed a standard procedure for manipulating expectancy in placebo research, where differing levels of expectancy are communicated verbally to participants.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Therapeutic treatments that are perceived as intrinsically satisfying tend to be rated as being more likely to be effective, so there is a confound between the expectancy of success and the intrinsic value of the treatment. Several studies have shown that motivational variables, namely dispositional optimism (Geers, Wellman, Fowler, Helfer, & France, ), gratitude (Geraghty, Wood, & Hyland, ) and the intrinsic satisfaction of the therapy and effort, are important contributors to outcome and that the effect of expectancy is mediated through these motivational variables (Gaitan‐Sierra & Hyland, , ). Previous studies demonstrating motivational concordance have not used clinical populations.…”
Section: Common Factor Mechanismsmentioning
confidence: 99%
“…One way to assess the effectiveness of a therapy is through its effects on the client's regulation of emotions and affect (Rottenberg & Gross, ) and which can be assessed by scales measuring mood. In line with this approach, previous studies have examined the impact of motivated behaviour on mood change by employing the Positive Affect and Negative Affect Schedule (PANAS) to measure global mood following therapeutic engagement (Gaitan‐Sierra & Hyland, , ). In the present research, we examine the effectiveness of therapeutic treatment using the PANAS, a scale that provides separate measures of positive and negative affect.…”
Section: Common Factor Mechanismsmentioning
confidence: 99%